Experiencing Rhythm in Dance - Wilson, John M.; Henley, Matthew (Frontiers in Psychology, 2022)
In this article, two dance educators offer a definition of rhythm from the modern and post-modern concert dance tradition and discuss pedagogical practices that bring students’ awareness to rhythm as a lived-experience. For the dancer, in the midst of the dance, rhythms are recurring patterns of measured energy. These patterns are nested in scales from the moment-to-moment shifts in neuromuscular contraction and release to the rise and fall of dramatic tension in a performed dance. This approach to rhythm often runs counter to many dance students’ studio-based training in which rhythm is equated to synchronizing accents to a counted meter. The authors describe pedagogical practices in the classroom that foster engagement with rhythm as lived-experience. After drawing attention to kinesthesis, or the awareness of movement, in general, students are encouraged to attend to and modulate levels of energy, or exertion, embedded in four primary movement qualities. As varying levels of exertion are attended to across temporal durations, students notice patterns as they emerge and recur. This attention to recurring patterns of measured energy is, the authors claim, the lived-experience of rhythm in modern and postmodern concert dance.